Power-aware routing in wireless sensor networks - Zha, Wei (2013)
Wireless sensor networks have drawn a lot of attention in recent years. Due to the advantages of flexibility and cheap cost, wireless sensor network applications have been widely used for both civil and military purposes. However, constrained by hardware, sensor nodes usually have limited energy supply. All wireless sensor network applications have to take energy issues into consideration. In this thesis, we explore energy efficiency in wireless sensor networks and focus on energy efficient routing protocols. Two kinds of routing protocols, spatial index based routing protocols and geographic based routing protocols, are studied. Spatial index based routing protocols are able to inquire a selected area without flooding the whole network. The drawbacks are the high cost of maintenance and the lack of scalability. Strategies which prolong sensor network lifespan by reducing maintenance cost is studied. Geographic based routing protocols, on the contrary, are quite scalable because the network is organized in a stateless manner. However, they are all designed for stationary networks. Releasing this assumption may fail to guarantee delivery. The deep causes of delivery failure in duty-cycling sensor networks are fundamentally investigated and formally analyzed. A general algorithm component is proposed to serve existing geographic routing algorithms to guarantee the success of packet delivery in duty-cycling sensor networks. Future work will continue studying practical implementations of geographic routing and explore some new areas, such as energy usage prediction and privacy preserving in wireless sensor networks.